2022
DOI: 10.1021/acsami.1c23647
|View full text |Cite
|
Sign up to set email alerts
|

Cogel Strategy for the Preparation of a “Thorn”-Like Porous Halloysite/Gelatin Composite Aerogel with Excellent Mechanical Properties and Thermal Insulation

Abstract: This work presents the preparation and property characterization of a biomass gelatin (GA)-based aerogel. Halloysite nanotubes (HNTs) were used to improve the mechanical strength, pore size distribution, and thermal stability of the aerogel. Polyethyleneimine (PEI) and (3-glycidyloxypropyl)­trimethoxysilane (GPTMS) were utilized to increase the interfacial interaction between HNTs and GA through chemical cross-linking. Green, sustainable, and low-cost composite aerogels were prepared by “cogel” and freeze-dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As far as known, the directional structure will impair the thermal insulation performance in a specific direction, because more heat chooses to transfer uninterruptedly along the directional paths [ 1 , 43 , 44 ]. For the prepared aerogel composites, heat transfer is inhibited in both the axial and radial directions due to the isotropic structure comprised of the nondirectional tortuous paths ( Figure 4 d,e), and the aerogel composites thus show good thermal insulation performance in both directions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as known, the directional structure will impair the thermal insulation performance in a specific direction, because more heat chooses to transfer uninterruptedly along the directional paths [ 1 , 43 , 44 ]. For the prepared aerogel composites, heat transfer is inhibited in both the axial and radial directions due to the isotropic structure comprised of the nondirectional tortuous paths ( Figure 4 d,e), and the aerogel composites thus show good thermal insulation performance in both directions.…”
Section: Resultsmentioning
confidence: 99%
“…Clay aerogels are ideal candidates for thermal insulation materials with low density, low thermal conductivity and good fire resistance, and recently have aroused much interest due to their cost-effective and eco-friendly freeze-drying process [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, pure clay aerogels are fragile and low-strength to satisfy the practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that organic aerogels, such as chitosan aerogels, 14−16 cellulose aerogels, 17,18 gelatin aerogels, 19 and polyimide aerogels (PIAs), 20 have better mechanical properties compared to inorganic aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they tend to be brittle and fragile, making them prone to cracking or breaking under compression. , Additionally, the fabrication process for these materials can be complex and expensive, limiting their availability in the intermediate temperature areas. Recent research has suggested that organic aerogels, such as chitosan aerogels, cellulose aerogels, , gelatin aerogels, and polyimide aerogels (PIAs), have better mechanical properties compared to inorganic aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Aerogels are open porous solid materials formed by self-assembly of nanostructures or molecular chains. Their pores are filled with a large amount of air medium and exhibit unique physical characteristics, such as low volume density, highly porous structure, large surface area, and low thermal conductivity, which are considered the most suitable properties in the field of heat insulation. A typical inorganic aerogel (SiO 2 ) exhibits extremely low thermal conductivity, but the poor mechanical properties limit wide practical applications . Some organic aerogels (for example, RF, PU, PI, etc) with good formability are suitable choices, but the synthesis processes are complex and involve toxic solvents and raw materials, which will cause environmental pollution problems. , Compared to these traditional aerogels, development of aerogels based on natural polymers has attracted extensive attention to partially replace petroleum-based derivatives. , Due to the abundant sources, low price, and sustainable environmental protection, they represent an important development direction for organic aerogels. , The as-prepared aerogel does not involve toxic compounds and complex chemical synthesis and exhibits a rich porous structure, better thermal insulation, and extensible chemical function. , However, there are some inherent shortcomings, such as flammable skeleton and inconspicuous mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%